2018
DOI: 10.2147/idr.s179134
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of ESBL-producing <em>E. coli</em> and <em>K. pneumoniae</em>: establishing virulence clusters

Abstract: ObjectiveTo genetically characterize clusters of virulence factors (VFs) among extended spectrum β-lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae and assess whether these clusters are associated with genetic determinants or clinical outcomes.MethodsOne hundred forty-eight E. coli and 82 K. pneumoniae clinical isolates were obtained from 213 patients in Paris, France. Isolates underwent ESBL characterization, MultiLocus Sequence Typing (MLST) typing and phylogenetic group identification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In paediatric patients, both highly virulent carbapenemresistant K. pneumoniae and highly virulent disinfectantresistant K. pneumoniae have been reported, but there are few reports in the literature of K. pneumoniae strains that are resistant to both antibiotics and disinfectants (Candan and Aksöz 2015;Aygun et al 2019;Surgers et al 2019). In this study, it was found that all 34 CRKP strains carried virulence genes and disinfectant resistance genes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In paediatric patients, both highly virulent carbapenemresistant K. pneumoniae and highly virulent disinfectantresistant K. pneumoniae have been reported, but there are few reports in the literature of K. pneumoniae strains that are resistant to both antibiotics and disinfectants (Candan and Aksöz 2015;Aygun et al 2019;Surgers et al 2019). In this study, it was found that all 34 CRKP strains carried virulence genes and disinfectant resistance genes.…”
Section: Discussionmentioning
confidence: 62%
“…In recent years, increasing attention has been given to K. pneumoniae, focusing on its high rate of drug resistance and high virulence. However, disinfectant resistance has received little attention among K. pneumoniae strains (Candan and Aksöz 2015;Aygun et al 2019;Surgers et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These cephalosporins include cefotaxime, ceftriaxone, and ceftazidime, as well as the oxyimino-monobactam aztreonam. Cefotaximases, characterized by CTX-M genes arose by plasmid transfer from pre-existing chromosomal ESBL genes from the bacteria Kluyver a spp., [ 9 ] CTX-M ESBLs now represent a large proportion of global ESBL strains and are the dominant ESBLs in the US, particularly among urinary tract infections [ 10 , 10 ].…”
Section: Classification and Evolution Of Carbapenem Resistancementioning
confidence: 99%
“…In the present study, CTX-M-27 was significantly more frequent in Beaujon (15.6%) than in Lucus Augusti (6.5%). However, the Beaujon's CTX-M-27 percentage appeared as remarkably higher than those found before 2014 (4.5-5.4%) in other 19 hospitals located as Beaujon in the Paris area (Robin et al, 2017;Surgers et al, 2019). Inversely, this percentage was closer to that found between 2014 and 2017 in 24 pediatric centers located in six French regions, i.e., 12.4% among 251 ESBL-EC isolated from febrile urinary tract infections (FUTIs) (Birgy et al, 2020).…”
Section: Discussionmentioning
confidence: 73%